Desenvolvimento de programa educacional multimídia para ensino-aprendizagem de retalho cutâneo - Sena, David Ponciano de (2012)
During the process of teaching and learning in surgery one should take into account the need to provide adequate teaching methodology, that is efficient, accessible and provides good cost-benefit training, also avoiding ethical conflicts with patients and animal models. The goal of this study is to develop and validate a multimedia software that assists in the teaching-learning rhomboid flap process. Fifty students from the fifth and sixth year of medical school completed a pretest and were randomly divided into two groups of 25 students each. For five minutes the control group studied a printed chapter of a standard book while the test group used a computer multimedia software, describing how to perform a rhomboid flap. Each group was evaluated in a blind manner by board certified surgeons (Brazilian Society of Plastic Surgery) using OSATS protocol (Objective Structured Assessment of Technical Skill) and answered a post-test. The control group was assessed a second time after studying for 5 minutes with the software. The group that used the multimedia software achieved higher scores on the practical performance and the post-test as compared to the control group. All students subjected to both methods rated the software as their choice method of learning.